PENGARUH MODEL PEMBELAJARAN INKUIRI TERBIMBING TERHADAP MOTIVASI DAN KEMAMPUAN PEMECAHAN MASALAH SISWA PADA MATERI POLA BILANGAN - Wulandari, Inayah; Hanifah, Umi; A'imah, Syarifatul (Program Studi Pendidikan matematika STKIP PGRI Pacitan STKIP PGRI Pacitan, 2024)
This research aims to determine the effect of the guided inquiry learning model on students' learning motivation and students' problem solving abilities on number pattern material for class 8 B students at MTs Miftahul Ulum Assimachi. The method used is a qualitative descriptive research method. This research was conducted at MTs Miftahul Ulum Assimachi, Grati District, Pasuruan Regency, with 28 students in class 8B for the 2023/2024 academic year. The guided inquiry learning model has a significant influence on the problem-solving abilities and learning motivation of class 8B students at MTs Miftahul Ulum Assimachi. This is shown by the average score obtained and the level of student activity increasing during learning with the guided inquiry model.